Avaliação da estabilidade de tensão nos sistemas de distribuição considerando a injeção de potência da geração distribuída - Alves, Alessandro Arjona (2016)
The huge rise in electricity energy demand seen in recent decades, the growing interest in alternative and renewable energy sources have placed the distributed generation (DG) in evidence in the global energy landscape. This scenario brings a significant growth in the use of this energy source. Thus, different types of interface and primary sources of energy, with the possibility of allocating different points in the network and with different capabilities, distributed generation brings different impacts to the distribution systems, including power system voltage stability. The voltage stability in networks with distributed generation is the object of this study. To this end, it has been studied methods for power flow calculation, the fundamental concepts of voltage stability and methods of analysis. The aim of this research is to evaluate the distributed generation impact on the voltage stability. Therefore, it has been evaluated some technical aspects such as power factor, location and generation capacity. Through the development of the analysis it was possible to highlight the relationship between improvement in stability margin and the benefit in reducing losses caused by GD. Also it was found that, with a view to improving the margin of voltage stability, it is more efficient to inject power in the network with the same power factor of the system equivalent load.